A produção do conhecimento do Serviço Social : para além da academia - Barroso, Elaine Almeida de Jesus (2016)
The focus of this study lies with the Social Service of knowledge production in Brazil, and to analyze productions entered social workers in non-academic areas. Therefore, studies were analyzed submitted / published in the Annals of the Brazilian Congress of Social Workers (CBAS), from 2001 to 2013, from the 10th to the 14th edition of CBAS. The relationships that permeate the production of knowledge and professional practice have the iterativity the Brazilian socio-historical formation, that exceeds the setting condition, it is active and promotes the development of social work that is reflected in the production of the profession knowledge. The historical aspects that outline the movement of the profession in interventional and academic environment impact production of knowledge of Social Work. Starting from this assumption argue are two hypotheses, namely: a) despite established the importance of investigative dimension in the documents-based profession, the professionals involved in non-academic occupational areas need further appropriation for the production of knowledge; b) although with an increase in the number of social workers entered production in these areas, there remains a significant failure of this production. In the development of this research were adopted methodological procedures that characterize it as state of the art, using bibliographic and documentary sources such as subsidies for analysis, which considered the quantitative and qualitative approach and was made in line with the dialectical method. The results show a connection with the literature on the subject in relation to the quantity of production, an increase over the issues. However, to delimit the production of the social worker entered into non-academic spaces sees the little representation of these professionals in this scenario, which strengthens the need for greater ownership of the theoretical and methodological dimension by these professionals to overcome segmentation category between "thinking" and "those who do."